Revolution and the Meaning of History: An Essay on the Myth of the Revolutionary Break and the "Logic" of History in Historiographical Thought - Tinková, Daniela (Dějiny – teorie – kritika, 2023)
This essay explores the interpretation of the French Revolution as symbolic break between "traditional" and "modern" society in 19th–20th centuries historiography. The revolution, seen as a "crossroads of history" by its participants at the time, whether supporters or opponents, forced thinkers to look for answers to the question of the direction, progress, continuity or discontinuity of the historical "process". I have tried to (re)construct several key interpretational schema that in turn were conditioned by political-ideological orientations. Basically there were four lines or "stories" – conservative, liberal, republican and socialist. The "conservative" version (from Burke to Gaxotti) rejected the revolution as a pathological phenomenon that deviated from the logic of the current of history. The liberal line more or less accepted the revolution, but only its first phase regarded as a revolution of freedom (1789–1792), from which liberalism derived its own legitimacy; it rejected the "democratic" phase of the revolution – the Terror – as a deviation from the logic of the (beneficial) revolution itself. Republican historiography emphasised and praised the initial phase of the First Republic (1792–1795), in this way providing support for the legitimising foundation of the Third Republic. Socialist historiography (especially in the 20th century) encouraged favourable re-evaluation of the period of Jacobin dictatorship and thus provided a logical link between the French Revolution and the Soviet Revolution. The final section of the article is devoted to FrançoisFuret, one of several contemporary historians who have tried to interpret the revolution in a different way that cuts right across the political spectrum (with a mention of the fact that in recent years yet more alternative ways of bridging the classic ideological-political views of the revolution have emerged).